The degree to which Cape Town millenial consumers in the Central Business District rely on social media when making purchasing decisions: a quantitative study - Myoli, Khanya (The IIE, 2017)
The internet along with social media has over the years progressed and improved the quality of people’s lives and that of business operating constructs (Kotler & Keller, 2011: 36). The implications of social media for businesses are more profound than that of civilians, especially within ecommerce. Accordingly the main purpose of this research is to describe and explore the degree in which Cape Town millennial consumers in the Central Business District rely on social media when making purchasing decisions. The literature conducted generates initial propositions of factors that influence the millennial consumers purchasing decision process. The study takes form of a quantitative study whereby 140 online surveys were distributed to participants who fell between the age brackets of 18 – 37 and were either based or worked in Cape Town’s central business district. The results were analysed to filter the main factors of influence and to determine and attempt to explain the relationships between the identified factors. The results of this analysis show that social media and online user generated content is of high importance to this target audience with Facebook and Instagram taking priority above all social media platforms. Furthermore it emphasises the importance of online and social media referrals during the millennial in Cape Town central business district decision making process.
Keywords: Social Media; Consumer Behaviour; E-commerce; Brands; Branding